2010
DOI: 10.1089/neu.2009.1227
|View full text |Cite
|
Sign up to set email alerts
|

Minozac Treatment Prevents Increased Seizure Susceptibility in a Mouse “Two-Hit” Model of Closed Skull Traumatic Brain Injury and Electroconvulsive Shock-Induced Seizures

Abstract: The mechanisms linking traumatic brain injury (TBI) to post-traumatic epilepsy (PTE) are not known and no therapy for prevention of PTE is available. We used a mouse closed-skull midline impact model to test the hypotheses that TBI increases susceptibility to seizures in a ''two-hit'' injury model, and that suppression of cytokine upregulation after the first hit will attenuate the increased susceptibility to the second neurological insult. Adult male CD-1 mice underwent midline closed skull pneumatic impact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“…Indeed, the majority of ECS studies on normal animals has shown that ECS has no effect on the activation/proliferation of microglia and astrocytes [34, 35] or even increases the glial activation/proliferation [38, 39]. Only one study has reported that ECS reduces the density of microglial process in the murine hippocampus [37] and one other has shown that ECS inhibits GFAP expression in the rat hippocampus [33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of ECS studies on normal animals has shown that ECS has no effect on the activation/proliferation of microglia and astrocytes [34, 35] or even increases the glial activation/proliferation [38, 39]. Only one study has reported that ECS reduces the density of microglial process in the murine hippocampus [37] and one other has shown that ECS inhibits GFAP expression in the rat hippocampus [33].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining challenge is to determine the magnitude of the seizure susceptibility increase that would unequivocally pinpoint individual animals that will develop epilepsy within a given period of time. Chrzaszcz et al (2010) Only the data collected at least 1 week post-injury are included. CCI, controlled cortical impact; ECS, electroconvulsive shock; FPI, fluid-percussion injury; n.d., no data; P, postnatal day; PTZ, pentylenetetrazol; TBI, traumatic brain injury; ED, epileptiform discharge; EEG, electroencephalogram; GABA, c-aminobutyric acid.…”
Section: Epilepsy Phenotype Is Similar After Tbi Induced By CCI or Lamentioning
confidence: 99%
“…1,22 Inasmuch as sequential injury produced additive effects on histopathological and functional outcome, our study is in principle similar to other injury models in which TBI was combined with controlled secondary insults to mimic the clinical scenarios of superimposed hypoxemia, 23,24 systemic hemorrhage, 25 polytrauma, 26 and seizures. 27 Others have also reported TBI consisting of simultaneous linear and angular head acceleration. 28,19 In the model by Marmarou and colleagues, 29 combined impact and linear acceleration produces robust diffuse axonal injury but not contusion.…”
Section: Discussionmentioning
confidence: 99%